Insights into heart failure hospitalizations, management, and services during and beyond COVID‐19 - Charman, Sarah J. (ESC Heart Fail, 2020)
Coronavirus disease 2019 (COVID‐19) is caused by severe acute respiratory syndrome coronavirus‐2. The clinical presentation of this virus mainly manifests in the respiratory system but may also lead to severe complications in the cardiovascular system. The global burden of COVID‐19 has led to an unprecedented need to gain further insight into patient outcomes, management, and clinical practice. This review aims to provide an overview of the current literature on heart failure (HF) hospitalizations, management, and care pathways for supporting patients during and beyond this pandemic. A literature review of five areas of interest was conducted and included: (i) HF hospitalization; (ii) recognizing the needs and supporting HF patients during COVID‐19; (iii) supporting rehabilitation services; (iv) transitioning to a telehealth framework; and (v) the need for evidence. Patients with new‐onset or existing HF are particularly vulnerable, but a significant reduction in HF hospital admissions has been reported. During these periods of uncertainty, the current care pathways for acute and elective cardiac patients have had to change with the relocation of HF services to protect the vulnerable and reduce transmission of COVID‐19. Optimizing community HF services has the potential to reduce the pressures on secondary care during the recovery from this pandemic. Telemedicine and virtual health care are emerging technologies and overcome the risk of in‐person exposure. Successful remote delivery of cardiac rehabilitation services has been reported during the pandemic. Delivery of a robust telehealth framework for HF patients will improve communication between clinician and patient. The reduction in HF admissions is a concern for the future and may result in unintended mortality. New‐onset and current HF patients must understand their diagnosis and future prognosis and seek help and support using the appropriate platform when needed. Realigning HF services and the use of telemedicine and virtual health care has great potential but needs to be carefully understood to ensure engagement and approval in this population to overcome barriers and challenges.